Real-time PCR validation of visually identified snapper Chrysophrys auratus (Sparidae) eggs - Dias, P.; Wakefield, Corey; Fairclough, D.; Jackson, G.; Travers, M.; Snow, M. (Wiley-Blackwell Publishing Ltd., 2016)
© 2016 The Fisheries Society of the British Isles.In this study, a total of 212 eggs were visually identified as snapper Chrysophrys auratus. Real-time PCR confirmed visual identification in 69% of cases but corroboration varied widely among plankton samples. The use of molecular tools to support visual identification prior to adopting daily egg production stock assessment methods should be considered.